The complement system - an introduction for undergraduates - Holers, Michael; Frazer-Abel, Ashley (Henry Stewart Talks, 2019)
Complement system and its pathways, Activators of complement, Immunoglobulin (Ig) isotypes, Telling the innate immune system who to eat, Host defence: opsonization, The amplification loop, Proposed modulation of complement in vivo, Complement killing, Effector mechanisms in complement activation